An approach to the evolution of Social Theory in Latin America - Ayamamani-Collanqui, Pascual (2022)
The purpose of this essay is to analyze the evolution of social theory in Latin America, which implies a brief approach to the trajectory, the role played and the theoretical orientations of social sciences in Latin America; in the understanding that the evolution of Latin American social theory is involved in the study of human society settled in the South of America continent, grouped in various associations, collectivities and/or institutions. It is an approximate reflection based on the review of literature, and due to its nature, a condensed exposition is made, whose interest is centered on the 'evolution' of social theory in Latin America and the challenges of the same in the contemporary Latin American context.